The Effect of Leadership, Organizational Commitment and Work Motivation on Employee Performance at The Education Office of Labuhanbatu Utara Regency - Amir Hasanuddin Siahaan; Syaipul Bahri; Muiz Fauzi Rambe (Jurnal Ilmiah Sumber Daya Manusia, 2022)
The success of an agency depends on the performance of employees. Employee performance is influenced by several factors, including leadership, organizational commitment, and motivation. The problem that will be studied in this research is whether there is an influence of leadership, organizational commitment and motivation on employee performance at the Education Office of Labuhanbatu Utara Regency either simultaneously or partially. This study aims to determine the effect of leadership, organizational commitment and motivation on employee performance at the Education Office of Labuhanbatu Utara Regency either simultaneously or partially. The sampling technique used the census method (saturated sample), which took all members of the population into the research sample, amounting to 42 people. The analytical model used in this research is validity and reliability test, classical assumption test, multiple regression analysis, partial hypothesis testing. Simultaneous hypothesis testing and coefficient of determination with the help of the IBM SPSS for windows 23.0 program. The results of the research using SPSS 23, the multiple regression equation Y = 41.997 + 0.385X1 + 0.213X2 + 0.349X3. Test the significance of the regression equation with the F testcount = 5, 115 with a significance value of 0.000 <0.05, which means that simultaneously there is a positive influence between leadership, organizational commitment and motivation on employee performance at the Education Office of Labuhanbatu Utara Regency either simultaneously or partially. The results of the partial test of the leadership variable obtained tcount = 5.550 with a significance value of 0.000 < 0.05, for the organizational commitment variable obtained t count = 3.870 with a significance value of 0.002 < 0.05 and the motivation variable obtained tcount = 4.310 with a significance value of 0.000 < 0.05. The magnitude of the coefficient of influence simultaneously between leadership, organizational commitment and motivation is 51.7%. Based on the results of the study, it can be concluded that leadership, organizational commitment and motivation have a positive influence on employee performance at the Education Office of Labuhanbatu Utara Regency.